Botulinum Toxin Type A and B for the Reduction of Hypersalivation in Children with Neurological Disorders: A Focus on Effectiveness and Therapy Adherence - Schroeder, A. Sebastian; Kling, Theresia; Huß, Kristina; Borggraefe, Ingo; Koerte, Inga K.; Blaschek, Astrid; Jahn, Klaus; Heinen, Florian; Berweck, Steffen (Neuropediatrics, 2012)
Botulinum toxin (BoNT) is an established treatment option to reduce hypersalivation in children with chronic neurological disorders. Objective of this study was (1) to discriminate differences in efficacy and safety of repeated interventions using BoNT with a focus on different preparations used and (2) to look for effectiveness and treatment adherence from a qualitative research perspective in this single-center cohort study. We prospectively assessed goal attainment scaling, drooling severity and frequency score and the number of towels/day before, and 4 to 8 weeks after intervention. A parent questionnaire assessed therapy-related effects on quality of life retrospectively. A total of 19 out of 34 patients received repeated injections of BoNT (106 total). Mean dose: 95 units onabotulinumtoxinA (Botox®), 2383 units rimabotulinumtoxinB (Neuro-/Myobloc®). Outcome parameters showed a distinct reduction in all treatment groups with a higher efficacy of riB. The child's need for care was reduced in 79% and social interaction improved in 84%. Main reason for discontinuation was “not enough effect” and “formation of antibodies.” riB showed to be more effective in reducing hypersalivation, but antibody-formation seems to be clinically relevant. Despite clinical efficacy treatment adherence is influenced by personal and environmental factors of parents and caretakers balancing the short-term clinical benefit versus the burden of intervention.
Keywords: hypersalivation; sialorrhea; children; botulinum toxin type A; botulinum toxin type B; treatment adherence